Sleep quality and duration and frailty in older adults: a systematic review - Souza, Ângela Maria Natal de; Fernandes, Dalila Pinto de Souza; Castro, Isabella Silva; Gróla, Fernanda Gaspar; Ribeiro, Andréia Queiroz (Frontiers in Public Health, 2025)
IntroductionSleep problems and frailty are associated with adverse health outcomes in older adults, including mortality, and constitute a major public health challenge.ObjectiveThis study investigated the association between sleep quality and duration and frailty in older adults, with emphasis on methods of evaluation.MethodsThis systematic review was guided by the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA). The Embase, Medline (Pubmed) and Cochrane libraries were searched, with no time restrictions for publications.Results and discussionOf the 17 studies included in this review, all published between 2009 and 2024, 13 were cross-sectional and only four were longitudinal. The Pittsburgh Sleep Quality Index and the Fried phenotype were widely used as methods to assess, respectively, sleep and frailty. Studies evaluating insomnia and frailty by the Fried phenotype all found an independent association. Poor sleep quality was independently associated with pre-frailty and frailty. Sleep onset insomnia, but not sleep maintenance insomnia, was associated with frailty. Short (5 h) and long (9 h) sleep duration were also associated with frailty. Poor sleep quality was associated with pre-frailty and frailty in older adults. The results show a wide diversity of methods for assessing both exposure (sleep quality) and outcome (frailty) and point to a need for further – especially longitudinal – research on the relationship between sleep and frailty.